Theory vs Reality: Making Environmental Use Rights Work in New Zealand - Kevin Guerin (New Zealand Government, The Treasury, 2004)
The potential advantages in flexibility and efficiency of environmental use rights (such as permits and quotas) over prescriptive regulatory approaches have been well surveyed, and are being advocated in New Zealand now as a tool for achieving sustainable development. So why have they not been more widely adopted here? How can government help remove barriers and improve both economic and environmental outcomes in New Zealand? At the structural level the barriers tend to be well known, or presumed, as a lack of statutory frameworks or central government guidance, and information costs involved in defining the resource and in determining an appropriate rights framework to optimise its use. Even given these structural and technical barriers there remains the task of explaining why, since those barriers are not insuperable, little progress has occurred. Other factors include the extent to which such responsibility in New Zealand is delegated by central government, competing priorities for regional governments, lack of pressure on resources (eg; water in much of New Zealand), the difficulty of making contentious choices and strength of existing interests, reluctance to acknowledge any private rights to some resources, the relative ease of using existing regulatory tools, and low benefits relative to costs in small markets particularly where geographical distinctions exist such as for water and certain types of pollution. This suggests that the best focus for central government may be on better guidance, filling gaps in legislative frameworks, and providing or encouraging provision of the necessary institutions and systems in ways that allow economies of scope and scale. It is unclear how much scope there is for improvement but getting rid of unnecessary barriers, as long as it is done without unnecessary elaboration or restriction, will help secure whatever gains are out there to be had.
Keywords: D23; H23; K11; P14; Q15; 330; Water; Property Rights; Transferability; Market Based Instruments